Factors Affecting Burnout and Turnover Intention of Nurse at Academic Hospitals in Covid 19 Pandemic - Mafula, Dluha; Retno Martani, Hersinta; Widyawati, Widyawati (Universitas Airlangga, 2023)
Introduction: The COVID-19 has caused an increase in workload that affects the physical and psychological health of nurses. Moreover, the ongoing increase of workload can trigger work fatigue and declining work motivation. The purpose of this research is to identify factors which influence burnout and turnover intention of nurses working in a academic hospital during the COVID-19 pandemic. Method: This research is non-experimental explanation survey research with cross sectional approach which involved 186 respondents who are chosen using convenience sampling. The independent variables are demographic factors while the dependent variables are burnout and turnover intention. Instrument used is a questionnaire related burnout and turnover intention which is based on a reference of earlier research. Data analysis used is multiple regression and logistic with p value â‰¤ 0,05. Result: Indicators influencing burnout were age (Coeff: -0.017; p=0.017), family dependents (Coeff: -0.799; p=0.011), and workshop on COVID-19 management (Coeff: 0.869; p=0.017). Indicators influencing turnover intention were family dependents (Coeff: -0,647; p=0.014), marital status (Coeff: 1.589; p=0.000), adjustment and arrangement of work schedule for COVID-19 service (Coeff: 0,901; p=0.033), and workshop on COVID-19 management (Coeff: 0,901; p=0.020). Conclusion: The research shows that turnover intention on nurses working in a academic hospital during the COVID-19 pandemic is mostly on moderate level, as well as with burnout. Health institutions must focus on applying strategies to reduce a nurse workload which include infection prevention action, personal protective equipment (PPE), regular workshops on current COVID-19 management, incentive allotment punctuality and flexible work schedule arrangement.